1981
DOI: 10.1007/bf00409456
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous absorption of griseofulvin and proquazone in the rat and in isolated human skin

Abstract: Ointments containing griseofulvin and proquazone, respectively, were made up of monoglycerides of medium chain length and an aprotic solvent, glycerinformal. The ointments were applied topically on the back of bile cannulated rats. The total amount absorbed percutaneously and the permeability constants of both drugs were considerably higher for the ointments than for simple solutions of the drugs without monoglycerides. Distribution of the labeled drugs in rat skin has been demonstrated by microautoradiography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…Whereas erythromycin is only slightly soluble in water (0Á1%) it is freely soluble in organic solvents such as alcohol, chloroform, ether, acetone, acetonitrile and benzyl alcohol, which might enable its transfer to the lipoidal components of cells and matrices. The results from microautoradiography seem similar to those of Franz et al (1981) who observed progressive disappearance of radioactivity from the surface and a route of penetration which initially seemed to occur adjacent to the pilosebaceous glands and skin appendages, followed by diffusion of the labelled molecules through the epidermis before subsequent capillary transport. The erythromycin dissolved in the TPDS might penetrate the skin by various routes.…”
Section: Concentration Of N-methyl[ 14 C]erythromycin In the Skinðradsupporting
confidence: 82%
See 2 more Smart Citations
“…Whereas erythromycin is only slightly soluble in water (0Á1%) it is freely soluble in organic solvents such as alcohol, chloroform, ether, acetone, acetonitrile and benzyl alcohol, which might enable its transfer to the lipoidal components of cells and matrices. The results from microautoradiography seem similar to those of Franz et al (1981) who observed progressive disappearance of radioactivity from the surface and a route of penetration which initially seemed to occur adjacent to the pilosebaceous glands and skin appendages, followed by diffusion of the labelled molecules through the epidermis before subsequent capillary transport. The erythromycin dissolved in the TPDS might penetrate the skin by various routes.…”
Section: Concentration Of N-methyl[ 14 C]erythromycin In the Skinðradsupporting
confidence: 82%
“…The dry slices were then stained with Paragon Blue. This is a variation of the methods of Franz et al (1981) and Sun et al (1994). Adjacent sections were also stained with haematoxylin±eosin.…”
Section: Animals and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…140,141 When creating novel formulations for griseofulvin, the urine excretion levels are also often investigated. 142,143 Recently, we have demonstrated a strong correlation between the in vivo degradation profile of vaterite carriers inside the hair follicles, intrafollicular storage of the loaded drug, and its excretion kinetics in urine. 46 Thus, here, the Gf excretion profiles were studied to assess the prolonged-release property of the designed carriers in vivo.…”
Section: Biomaterials Sciencementioning
confidence: 99%
“…Some GEFA derivatives were reported as enhancers of the percutaneous absorption of drugs. 26,27) Figure 1 shows the effect of the substitution degree of the caprylic chain in GEFA-C 8 on the skin permeation of PTZ. GEFA-DiC 8 and GEFATriC 8 did not have an enhancing effect on the skin permeation of PTZ.…”
Section: Screening Test For Effective Enhancersmentioning
confidence: 99%